(untitled) (African Journal of Biomedical Research, 2023)
This study investigated the plausible role of angiotensin II receptor on vascular mechanism underlying the pathophysiology of salt-induced hypertension in rats exposed to high environmental temperature chronically. Aortic rings were obtained from seven groups of male Sprague Dawley rats (n=6) including control rats (I) fed with 0.3% NaCl diet (normal diet, ND); salt-loaded rats (II) fed with 8% NaCl high salt diet (HSD); ND rats (III) exposed to HET (38.5±0.5 oC) 4 hours daily per week; rats (IV) fed with 8% NaCl diet and exposed to HET daily; rats (V) fed with 8% NaCl diet and treated with telmisartan (30mg/kg); ND rats (VI) exposed to HET and treated with telmisartan; rats (VII) fed with 8% NaCl diet, exposed to HET and treated with telmisartan. Photomicrography study was conducted on the first set of rings and the second set of rings were pre-contracted with Norepinephrine (NE) at 10-4 or 10-5, M to obtain a maximum peak contractile response, followed by the assessment of vascular relaxation response to graded doses of acetylcholine (Ach) and sodium nitroprusside (SNP) respectively from10 -9 to 10-4 M in endothelial intact aortic rings. Vascular relaxation to Ach and SNP were impaired in rings of rats fed a HSD and exposed to HET respectively and combined, with non-synergistic response. But in contrast, contractile response to NE in vessels with combined exposure was synergistic, but mitigated by telmisartan, an angiotensin II receptor blocker, ditto for the photomicrograph of the vessels. Angiotensin II blockade with telmisartan partly mitigated the deleterious vascular impact of combined exposure to high salt diet and environmental heat.